Psychological aspects of perception of scientific terms in English - Ruzmetova, Dildora (The Lingua Spectrum, 2025)
This article examines the psychological and linguistic foundations of knowledge acquisition and lexical development within the foreign-language learning process. It explores key cognitive mechanisms such as perception, attention, and apperception, highlighting their influence on learners’ ability to comprehend and internalize new lexical items. Various scholars’ classifications of learning stages – including perception, understanding, memorization, and active application – are discussed and compared. The study emphasizes the importance of transposition, semantic clarification, and visualization strategies in facilitating effective vocabulary learning. Special attention is given to the reproductive level of mastery, where learners demonstrate their ability to apply newly acquired vocabulary in unfamiliar communicative contexts. Such ability is interpreted as an indicator of cognitive development and deeper linguistic competence. The article aims to identify effective didactic approaches that consider psychological processes in foreign-language acquisition and support the enhancement of students’ professional and academic lexical skills.